Neglected Islamic Civilization? Muslim Intellectual Network in Mindanao, Philippines 19th Century in Aleem Ulomuddin Said Manuscript Collection - Raya, Moch. Khafidz Fuad; Samsodden, Johaina Ali (Universitas Nahdlatul Ulama Surabaya, 2022)
This article attempts to fill a research gap on the development of Islam in Mindanao, Southern Philippines, in the 19th century, where Muslim traditions in the region were well established and connected with Muslim intellectuals in other Islamic worlds. This relates mainly to a set of primary sources of Islamic manuscripts recently discovered by scholars such as Gallop, Fathurrahman, and Kawashima in the Mindanao area, which previously belonged to a local Maranao ‘ulamā’, named Shaykh Aleem Ulomuddin Said. This collection of manuscripts is written in three languages: Malay, Arabic, and Maranao, which contains various fields (al-Qur’ān studies, ḥadīth, tafsir, tasawuf, prayer, and ajimat, akidah and theology, and Arabic morphology). Using a qualitative approach and philological research methods, the findings of this study indicate that these Islamic manuscripts show the close relationship of Mindanao Muslim networks during the 18th and 19th centuries with their other Malay counterparts, such as those in Aceh, Banten, Cirebon, and Minangkabau. It also confirmed its network with the wider Islamic world in the Middle East region (Mecca, Medina, and Yemen) through the Sufi order of Shaṭṭārīyah, and influenced the intellectual tradition until the 19th century. Artikel ini mencoba mengisi gap research yang sangat terbatas tentang perkembangan Islam di Mindanao, Filipina Selatan pada abad ke-19 dimana tradisi Muslim di wilayah tersebut sudah mapan dan terhubung dengan intelektual Muslim di dunia Islam lainnya. Ini terutama berkaitan dengan satu set sumber utama manuskrip Islam yang baru-baru ini ditemukan oleh cendikiawan seperti Gallop, Fathurahman, dan Kawashima di daerah Mindanao, yang sebelumnya milik seorang ‘ulamā lokal Maranao, yang bernama Syaikh Aleem Ulomuddin Said. Koleksi manuskrip ini ditulis dengan tiga bahasa yaitu bahasa Melayu, Arab, dan Maranao yang berisi berbagai bidang (studi al-Qur’ān, ḥadīth, tafsir, tasawuf, doa dan ajimat, akidah dan teologi, serta morfologi Arab). Dengan menggunakan pendekatan kualitatif dan metode penelitian filologi, temuan penelitian ini menunjukkan bahwa manuskrip-manuskrip Islam ini menunjukkan hubungan erat jaringan Muslim Mindanao selama abad ke-18 dan 19 dengan rekan-rekan Melayu mereka lainnya seperti di Aceh, Banten, Cirebon, dan Minangkabau. Hal ini juga menegaskan jaringan mereka dengan dunia Islam yang lebih luas, lebih khusus lagi dengan wilayah Timur Tengah (Mekah, Madinah, dan Yaman) melalui tarekat Sufi Shaṭṭārīyah, dan berpengaruh terhadap tradisi intelektual sampai abad ke-19.